Food for thought: a qualitative assessment of medical trainee and faculty perceptions of nutrition education - Olivia Kunitsky; Mahdi Taye; Karla Feeley; Hugh Johnson; Abigail Glynn; Avery Stivale; Matthew Hamers; Alexis Notarianni; Sireesha Mamillapalli; Gabi Waite; Sonia Lobo (BMC Medical Education)
Abstract Background The American Society of Clinical Nutrition recommends 37 to 44 h of undergraduate medical nutrition education. The Total Health Curriculum at Geisinger Commonwealth School of Medicine (GCSOM) contains 14 h of objective-based nutritional instruction. This study aimed to examine the perceptions of key stakeholders regarding the role of nutrition in medicine and to identify barriers, opportunities for improvement, and roles/responsibilities for innovative implementation of nutrition education. Methods This exploratory, qualitative study employed a phenomenological approach and inductive coding process. Purposive sampling recruited medical students, undergraduate medical education (UME) faculty, physicians, and other healthcare professionals at GCSOM and affiliated clinical sites. Semi-structured focus groups and one-on-one interviews were conducted via videoconferencing. Audio recordings were transcribed using NVivo 14. Transcripts were manually reviewed alongside the audio files to ensure accuracy. Data were systematically organized using the qualitative research methodology Rigorous and Accelerated Data Reduction (RADaR). Microsoft Copilot was used to assist with thematic analysis. Outcomes were compared, and consensus was obtained among raters. Results Twenty-five individuals were interviewed: 12 UME faculty, five students, and eight healthcare professionals, including two physicians. Participants included 18 females and seven males, aged 23 to 69 years. 92% of participants believed that all physicians should receive nutrition education and 40% felt unsatisfied with their nutritional training. For barriers, the qualitative analysis identified these themes: (1) time constraints, (2) assessment and prioritization, (3) insufficient faculty expertise, and (4) bias and stigma. For improvement opportunities, the qualitative analysis identified these themes: (1) curriculum design, (2) practical application, (3) patient-centered approach, and (4) trainee perceptions. For roles/responsibilities, the qualitative analysis identified these themes: (1) accreditation bodies, (2) stakeholder involvement, (3) public policy and legislation, and (4) multilevel responsibility. Conclusion Participants acknowledged a need for more medical nutrition education to prepare physicians who are equipped to manage the nutritional needs of patients. They recognized key challenges hindering the advancement of such education, proposed various forms of improvement, and identified roles for successful implementation. Future research will assess community perspectives and expand sample diversity.